circ-PRKCI targets miR-1294 and miR-186-5p by downregulating FOXK1 expression to suppress glycolysis in hepatocellular carcinoma - Chen, Wenqi (Mol Med Rep, 2021)
Numerous human circular RNAs (circRNAs/circ) have been functionally characterized. However, the potential role of circ-protein kinase C iota (PRKCI) in hepatocellular carcinoma (HCC) remains unknown. The effects of each transfection and expression levels of circ-PRKCI, microRNA (miR)-1294, miR-186-5p and forkhead box K1 (FOXK1) in HCC cells were analyzed using reverse transcription-quantitative PCR analysis. The interactions between circ-PRKCI and miR-1294 or miR-186-5p, and miR-1294 or miR-186-5p and FOXK1 were validated using dual luciferase reporter assays. The viability, invasion and migration of HCC cells were determined using Cell Counting Kit-8, Transwell and wound healing assays, respectively. The expression levels of FOXK1, hexokinase-2 (HK2), glucose transporter 1 (GLUT1) and lactate dehydrogenase A (LDHA) in HCC cells were analyzed using western blotting. The levels of glucose and lactic acid in the cultured supernatant were detected using commercially available kits. The results of the present study revealed that miR-1294 and miR-186-5p expression levels were downregulated in the HCC cell line, HCCLM3, and were subsequently downregulated by circ-PRKCI overexpression and upregulated by the knockdown of circ-PRKCI. circ-PRKCI overexpression promoted the viability, invasion and migration of HCCLM3 cells, which was also reversed by the overexpression of miR-1294 and miR-186-5p. In addition, the overexpression of circ-PRKCI upregulated FOXK1 expression levels, while the overexpression of miR-1294 and miR-186-5p downregulated FOXK1 expression levels. Conversely, the knockdown of circ-PRKCI expression downregulated FOXK1 expression levels, while the knockdown of miR-1294 and miR-186-5p upregulated FOXK1 expression levels. Furthermore, circ-PRKCI was identified to target miR-1294 and miR-186-5p, and miR-1294 and miR-186-5p were subsequently found to target FOXK1. The overexpression of circ-PRKCI also increased glucose and lactic acid levels, while the knockdown of FOXK1 decreased glucose and lactic acid levels. The knockdown of circ-PRKCI decreased glucose and lactic acid levels, which were reversed by FOXK1 overexpression. In conclusion, the findings of the present study suggested that circ-PRKCI may promote the viability, invasion and migration of HCC cells by sponging miR-1294 and miR-186-5p to upregulate FOXK1 expression levels.